2010
DOI: 10.1029/2009jg000995
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of forest height and biomass from multisensor data fusion

Abstract: [1] Elevation data acquired from radar interferometry at C-band from SRTM are used in data fusion techniques to estimate regional scale forest height and aboveground live biomass (AGLB) over the state of Maine. Two fusion techniques have been developed to perform post-processing and parameter estimations from four data sets: 1 arc sec National Elevation Data (NED), SRTM derived elevation (30 m), Landsat Enhanced Thematic Mapper (ETM) bands (30 m), derived vegetation index (VI) and NLCD2001 land cover map. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Statistical analysis has been a common method of fitting the biomass-height relationship. Widely used regression models include power [Chave et al, 2005;Köhler and Huth, 2010;Mitchard et al, 2011;Saatchi et al, 2011;Wang et al, 2013], linear [Fang et al, 2006;Skowronski et al, 2007], the quadratic polynomial [Lefsky et al, 2005b], and exponential functions [Yu et al, 2010]. Previous studies have shown that biomass-height relationships differ greatly across environmental gradients and among different forest types [Drake et al, 2003;Pan et al, 2004;Wang et al, 2013].…”
Section: Methods 221 Estimating Forest Stand Agementioning
confidence: 99%
“…Statistical analysis has been a common method of fitting the biomass-height relationship. Widely used regression models include power [Chave et al, 2005;Köhler and Huth, 2010;Mitchard et al, 2011;Saatchi et al, 2011;Wang et al, 2013], linear [Fang et al, 2006;Skowronski et al, 2007], the quadratic polynomial [Lefsky et al, 2005b], and exponential functions [Yu et al, 2010]. Previous studies have shown that biomass-height relationships differ greatly across environmental gradients and among different forest types [Drake et al, 2003;Pan et al, 2004;Wang et al, 2013].…”
Section: Methods 221 Estimating Forest Stand Agementioning
confidence: 99%
“…SAR remote sensing is no exception regarding the issue of uncertainty in the analysis in addition to other complexities and ambiguities that are specific to SAR techniques. Several other limitations of SAR are as follows: (1) costly data, (2) temporal repeativity, (3) Santoro et al 2006;Yu et al 2010;Le Toan et al 2011;Hamdan et al 2011;Englhart et al 2012;etc. Fransson et al 2001;Santoro et al 2003;Kumar 2009;etc. Approach 2: Based on sensor type Single Multiple/ Synergic Nizalapur et al 2010;Hamdan et al 2011;Wollersheim et al 2011;Carreiras et al 2013;etc.…”
Section: Limitations and Uncertaintiesmentioning
confidence: 99%
“…Equation (4) indicates that a large forest patch with great PCH has a larger weight and thus a larger structuring element size.…”
Section: Refined Gld: Gldmentioning
confidence: 99%